FAKTOR NON FINANSIAL DAN FINANSIAL YANG BERPENGARUH TERHADAP NILAI (Studi Empiris pada Perusahaan Perbankan yang Terdaftar pada BEI Tahun 2017-2019) - Tamara Aulia; Darsono Darsono (Diponegoro Journal of Accounting, 2022)
This study aims to examine financial factors, including capital structure, firm size and dividend policy as well as non-financial factors, i.e. intellectual capital, management risk disclosure, and management structure on firm value. Firm value is proxied by Tobin's Q.The data are collected by documentation method. The research sample is banking industry that listed in the Indonesia Stock Exchange during 2017-2019. The sample method used is a purposive sampling method. The samples that eligible in the study are 104 firm-years. The data analysis technique used is multiple linear regression.The results showed that the disclosure of risk management, capital structure and dividend policy have effect on firm value, while for intellectual capital, management structure and firm size have no effect.